ANALISIS KINERJA DITINJAU DARI SEGI TINGKAT LIKUIDITAS DAN PROFITABILITAS PADA PT. PLN MAKASSAR - Adriani Adriani (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2013)
The purpose of this study was to menegetahui how much liquidity and profitability levels at the Department of Finance and Asset Management Revenue Pinrang area of 2010 to 2012. The results of this study in katakana liquid liquidity ratio in 2010 because the current ratio was 2.74% in value in 2011 and 2012 because the liquid is not classified as Current ratio is 1.35% and 1.72%. Based on the profit level of profitability ratio fluctuated in 2010 until 2012. So the profitability ratio increased in 2012 from 2010 and 2011. Ratio Profotabilitasnya then was successful at the Department of Finance and Asset Management Revenue Pinrang area of 2010 to 2012.